Implementation of SCADA in Cartoner Machine - Prasad Tripathy, Hara; Pattanaik, Priyabrata (International Journal of Psychosocial Rehabilitation, 2025)
this paper proposes the implementation of SCADA for using visual basic in a cartoner packaging machine for a variety of reasons. A very less number of parameters of an input user are required by SCADA applications and data monitoring, logging and functionalities that are to be visualised by a user. Most of the functionality is provided by SCADA based solutions but at a cost higher than that for OEM customers. SCADA applications and industrial HMI are created by OEMs, users, integrators and developers visualized by a user. The view of industrial process in real time commensurate SCADA based on VB, downtime is reduced and also the troubleshooting time for faults are reduced. The visualization gets easier when OEM industries adapt to customized SCADA